Assessment of the Association Between Neuraxial Anesthesia and Back Pain After Delivery: A Systematic Review and Meta-Analysis - Sara Timerga; Getaw Walle; Wondwosen Mebratu; Aynalem Befkadu (Anesthesiology Research and Practice)
Conclusion: Our result suggests neuraxial anesthesia may not be the cause or the risk factor for the overwhelmingly high incidence of back pain women experience after delivery.